Prognostic Value of C-Reactive Protein, Glasgow Prognostic Score, and C-Reactive Protein-to-Albumin Ratio in Colorectal Cancer - Zhou, Jiahui; Wei, Wene; Hou, Hu; Ning, Shufang; Li, Jilin; Huang, Baoyue; Liu, Kaisheng; Zhang, Litu (Frontiers in Cell and Developmental Biology, 2021)
Background: Emerging evidence suggests that inflammatory response biomarkers are predictive factors that can improve the accuracy of colorectal cancer (CRC) prognoses. We aimed to evaluate the prognostic significance of C-reactive protein (CRP), the Glasgow Prognostic Score (GPS), and the CRP-to-albumin ratio (CAR) in CRC. Methods: Overall, 307 stage I–III CRC patients and 72 colorectal liver metastases (CRLM) patients were enrolled between October 2013 and September 2019. We investigated the correlation between the pretreatment CRP, GPS, and CAR and the clinicopathological characteristics. The Cox proportional hazards model was used for univariate or multivariate analysis to assess potential prognostic factors. A receiver operating characteristic (ROC) curve was constructed to evaluate the predictive value of each prognostic score. We established CRC survival nomograms based on the prognostic scores of inflammation. Results: The optimal cutoff levels for the CAR for overall survival (OS) in all CRC patients, stage I–III CRC patients, and CRLM patients were 0.16, 0.14, and 0.25, respectively. Kaplan–Meier analysis and log-rank tests demonstrated that patients with high CRP, CAR, and GPS had poorer OS in CRC, both in the cohorts of stage I–III patients and CRLM patients. In the different cohorts of CRC patients, the area under the ROC curve (AUC) of these three markers were all high. Multivariate analysis indicated that the location of the primary tumor, pathological differentiation, and pretreatment carcinoembryonic antigen (CEA), CRP, GPS, and CAR were independent prognostic factors for OS in stage I–III patients and that CRP, GPS, and CAR were independent prognostic factors for OS in CRLM patients. The predictors in the prediction nomograms included the pretreatment CRP, GPS, and CAR. Conclusions: CRP, GPS, and CAR have independent prognostic values in patients with CRC. Furthermore, the survival nomograms based on CRP, GPS, and CAR can provide more valuable clinical significance.